2013
DOI: 10.5194/nhess-13-2891-2013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of targeted observations on short-term forecasts of high-impact weather events in the Mediterranean

Abstract: Abstract. The influence of targeted observations on shortrange forecasts is tested over two different periods of PRE-VIEW (2008) and MEDEX (2009) data targeting field campaigns for a set of Mediterranean high-impact weather events. As targeted observations we have used not only extra radiosondes, but also enhanced satellite data observed in singular vector (SV)-based sensitive regions. Three parallel observing system experiments, based on the High-Resolution Limited-Area Model (HIRLAM) data assimilation and f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Another way is to analyse the direct impact on the forecast of the additional observations or even of the additional assimilation of some available and unused data, like high-density satellite data (Campins et al, 2013). The results obtained until now are not conclusive, but indicate the partial usefulness of some additional data.…”
Section: Targeted Observation and Impact Of Additional Observationsmentioning
confidence: 99%
“…Another way is to analyse the direct impact on the forecast of the additional observations or even of the additional assimilation of some available and unused data, like high-density satellite data (Campins et al, 2013). The results obtained until now are not conclusive, but indicate the partial usefulness of some additional data.…”
Section: Targeted Observation and Impact Of Additional Observationsmentioning
confidence: 99%
“…The results obtained by Campins et al (2013) have shown a distinct impact of targeted data during DTS- PREVIEW-2008 andDTS-MEDEX-2009. It was argued that it was due to the distinct weather regimes that dominate over each period and the existing composite observing system.…”
Section: Introductionmentioning
confidence: 91%
“…The set-up and verification methods employed in these observing system experiments follow closely those performed previously by Campins et al (2013) to test the influence of radiosondes deployed during the DTS-PREVIEW-2008 and DTS-MEDEX-2009 campaigns on the forecasting of high-impact weather in the Mediterranean.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 2 more Smart Citations